Legal Politics Formation of Act No.17 of 2019 concerning Water Resources - Muhammad RM Fayasy Failaq; Arsyad Surya Pradana (LEGAL BRIEF, 2023)
Act No. 17 of 2019 concerning Water Resources is a very dynamic legal product. Its formation has many influencing factors, one of which is the Constitutional Court Decision No. 85/PUU-XI/2013 which canceled Law no. 7 of 2004 and restore the enactment of Law no. 11 of 1974 concerning Irrigation. In implementing Law no. 11 of 1974 was considered incapable of being the basis for regulating water resources, so that since 2017 the Academic Paper of the Water Resources Bill has begun to be drafted. The study will focus on the formation of Law no. 17 of 2019 by using legal politics as a knife for analysis. The research method is juridical-normative with the type of library research to examine secondary sources with legal and historical approaches. The results of this study are that there are differences and developments in the style of laws related to water resources that apply in Indonesia, starting from the first with a centralized pattern to the latter becoming decentralized with the domination of permits by the center. The dynamics of the legislation of this Law runs smoothly with the forming factors which include Article 33 of the 1945 Constitution of the Republic of Indonesia, MK Decision No. 85/PUU-XI/2013, RPJP 2005-2025, RPJMN 2015-2019, and Study of the Water Resources Bill in Academic Papers. Lastly, this law was born in a democratic political configuration and the characteristics of its legal products are responsive even though it still adheres to the concept of water privatization which is rejected by several parties